Respons Antibodi Anti ETEC K99 pada Induk Sapi Bunting Setelah Pemberian Vaksin Escherichia Coli Polivalen - Anita Esfandiari; Sus Derthi Widhyari; Sri Murtini; Bayu Febram; Retno Wulansari; Leni Maylina (Jurnal Ilmu Pertanian Indonesia, 2014)
The objective of this experiment was to detect antibody (IgG) against enterotoxigenic Escherichia coli (ETEC)K99 in the blood of cows vaccinated by Escherichia coli polyvalent vaccine. Eight dry cows were injectedsubcutaneously by polyvalent Escherichia coli twice prior to parturition. Before vaccinated, the cows were givenimmunomodulator orally for 3 days. Blood samples were drawn from coccigeal vein prior to the 1st vaccination,two week following the 1st vaccination and at 1, 2, and 4 weeks after the 2nd vaccination. Blood samples wereanalyzed for IgG and ETEC K99 using indirect Enzyme Linked Immunosorbent Assay (ELISA) assay. Results of theexperiment indicated that absorbance values of all vaccinated cows before the first vaccination until third weekfollowing the 2nd vaccination were below cut off values. The absorbance values then increased and were above cutoff values at fourth week following the 2nd vaccination. In conclusion, antibody against ETEC K99, were detected inthe blood of cows, fourth week following the 2nd vaccination.